Analysis and prediction of seed quality using machine learning - Raghavendra Srinivasaiah; Meenakshi Meenakshi; Ravikumar Hodikehosalli Chennegowda; Santosh Kumar Jankatti (Institute of Advanced Engineering and Science, 2023)
The mainstay of the economy has always been agriculture, and the majority of tasks are still carried out without the use of modern technology. Currently, the ability of human intelligence to forecast seed quality is used. Because it lacks a validation method, the existing seed prediction analysis is ineffective. Here, we have tried to create a prediction model that uses machine learning algorithms to forecast seed quality, leading to high crop yield andÂ high-quality harvests. For precise seed categorization, this model was created using convolutional neural networks and trained using the seed dataset. Using data that can be used to forecast the future, this model is used to learn about whether the seeds are of premium quality, standard quality, or regular quality. While testing data are employed in the algorithmâ€™s predictive analytics, training data and validation data are used for categorization reasons. Thus, by examining the training accuracy of the convolution neural network (CNN) model and the prediction accuracy of the algorithm, the projectâ€™s primary goal is to develop the best method for the more accurate prediction of seed quality.